Discover new perspectives and gain insights with IDNLearn.com's diverse answers. Join our Q&A platform to access reliable and detailed answers from experts in various fields.
Sagot :
To determine the solution to the given system of equations, we need to analyze the system for consistency and solvability. Let's rewrite the system for clarity:
[tex]\[ \begin{array}{c} 2x - y + 3z = 8 \\ x - 6y - z = 0 \\ -6x + 3y - 9z = 24 \end{array} \][/tex]
Let's analyze this system step-by-step.
### Step 1: Represent the System in Matrix Form
First, write the coefficients in an augmented matrix form:
[tex]\[ \begin{bmatrix} 2 & -1 & 3 & | & 8 \\ 1 & -6 & -1 & | & 0 \\ -6 & 3 & -9 & | & 24 \end{bmatrix} \][/tex]
### Step 2: Simplify Using Row Operations
We shall row reduce the matrix to find if it is consistent.
1. Swap rows if necessary: The first row is already in a suitable form.
2. Eliminate [tex]\(x\)[/tex] from the second and third rows:
[tex]\[ \text{R2} \leftarrow \text{R2} - \frac{1}{2} \text{R1} \Rightarrow (1 - \frac{1}{2}(2))x + (-6 + \frac{1}{2}(1))y - (1 + \frac{1}{2}(3))z = 0 - \frac{1}{2}(8) \][/tex]
[tex]\[ \Rightarrow 0x + (-6.5)y + (-2.5)z = -4 \][/tex]
[tex]\[ \Rightarrow \begin{bmatrix} 2 & -1 & 3 & | & 8 \\ 0 & -6.5 & -2.5 & | & -4 \\ -6 & 3 & -9 & | & 24 \end{bmatrix} \][/tex]
[tex]\[ \text{R3} \leftarrow \text{R3} + 3 \cdot \text{R1} \Rightarrow (-6 + 6)x + (3 - 3)y + (-9 + 9)z = 24 + 24 \][/tex]
[tex]\[ \Rightarrow 0x + 0y + 0z = 48 \][/tex]
[tex]\[ \Rightarrow \begin{bmatrix} 2 & -1 & 3 & | & 8 \\ 0 & -6.5 & -2.5 & | & -4 \\ 0 & 0 & 0 & | & 48 \end{bmatrix} \][/tex]
### Step 3: Analyze the Result
From the matrix, we can see the last row translates to [tex]\(0 = 48\)[/tex]. This is a contradiction since there is no value of [tex]\(x\)[/tex], [tex]\(y\)[/tex], or [tex]\(z\)[/tex] that can satisfy this equation.
Therefore, the system of equations is inconsistent and has no solution. This corresponds to answer:
C. No solution
[tex]\[ \begin{array}{c} 2x - y + 3z = 8 \\ x - 6y - z = 0 \\ -6x + 3y - 9z = 24 \end{array} \][/tex]
Let's analyze this system step-by-step.
### Step 1: Represent the System in Matrix Form
First, write the coefficients in an augmented matrix form:
[tex]\[ \begin{bmatrix} 2 & -1 & 3 & | & 8 \\ 1 & -6 & -1 & | & 0 \\ -6 & 3 & -9 & | & 24 \end{bmatrix} \][/tex]
### Step 2: Simplify Using Row Operations
We shall row reduce the matrix to find if it is consistent.
1. Swap rows if necessary: The first row is already in a suitable form.
2. Eliminate [tex]\(x\)[/tex] from the second and third rows:
[tex]\[ \text{R2} \leftarrow \text{R2} - \frac{1}{2} \text{R1} \Rightarrow (1 - \frac{1}{2}(2))x + (-6 + \frac{1}{2}(1))y - (1 + \frac{1}{2}(3))z = 0 - \frac{1}{2}(8) \][/tex]
[tex]\[ \Rightarrow 0x + (-6.5)y + (-2.5)z = -4 \][/tex]
[tex]\[ \Rightarrow \begin{bmatrix} 2 & -1 & 3 & | & 8 \\ 0 & -6.5 & -2.5 & | & -4 \\ -6 & 3 & -9 & | & 24 \end{bmatrix} \][/tex]
[tex]\[ \text{R3} \leftarrow \text{R3} + 3 \cdot \text{R1} \Rightarrow (-6 + 6)x + (3 - 3)y + (-9 + 9)z = 24 + 24 \][/tex]
[tex]\[ \Rightarrow 0x + 0y + 0z = 48 \][/tex]
[tex]\[ \Rightarrow \begin{bmatrix} 2 & -1 & 3 & | & 8 \\ 0 & -6.5 & -2.5 & | & -4 \\ 0 & 0 & 0 & | & 48 \end{bmatrix} \][/tex]
### Step 3: Analyze the Result
From the matrix, we can see the last row translates to [tex]\(0 = 48\)[/tex]. This is a contradiction since there is no value of [tex]\(x\)[/tex], [tex]\(y\)[/tex], or [tex]\(z\)[/tex] that can satisfy this equation.
Therefore, the system of equations is inconsistent and has no solution. This corresponds to answer:
C. No solution
We appreciate your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. Thank you for choosing IDNLearn.com. We’re dedicated to providing clear answers, so visit us again for more solutions.